Social Workers as Collaborators? The Ethics of Working Within Australia's Asylum System*. Issue 2 (3rd April 2018) - Maylea, Christopher; Hirsch, Asher
ABSTRACT: Social workers working within the Australian asylum seeker processing system, particularly offshore on Nauru and Manus Island, risk being collaborators in the systemic abuse of men, women and children who seek asylum in Australia. In order to avoid accusations of collaboration, social workers must work to end this abuse. However, the current policy environment makes this very difficult, with social workers who resist the status quo risking unemployment, public shaming and imprisonment. Using freedom of information disclosures, whistleblower testimony, leaked documents, parliamentary records, case law, media reports and academic literature, this paper examines this difficult position. Alternatives to retreating from the system are proposed, including advocacy through whistleblowing, policy reform and litigation, or subversive action from within. Social workers are encouraged to act in whatever ways they can, within the ethical, legal and practical limitations which are imposed.